1992
DOI: 10.7326/0003-4819-117-2-124
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcome of Patients with Relapsed and Refractory Germ Cell Tumors Treated with High-Dose Chemotherapy and Autologous Bone Marrow Rescue

Abstract: Treatment with high-dose carboplatin and etoposide in conjunction with autologous bone marrow rescue in patients with relapsed or refractory germ cell tumors is a potentially curative therapeutic option, even for heavily pretreated or cisplatin-refractory patients. Some degree of disease resistance to cisplatin can be overcome with dose escalation of platinum compounds. Patients with multiple recurrences of relapsed or refractory primary mediastinal germ cell tumors were not helped by this approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
64
0
1

Year Published

1997
1997
1999
1999

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 157 publications
(66 citation statements)
references
References 15 publications
1
64
0
1
Order By: Relevance
“…The most significant prognostic factor found in this study was disease status at the time of HDT; patients who had either failed to achieve an initial CR with first-line therapy or had chemotherapysensitive relapse had a significantly better outcome that those with resistant relapse. These findings concur with previous studies that have reported HDT in chemotherapy-responsive patients (Barnett et al, 1993;Margolin et al, 1996) and in patients with resistant relapse (Broun et al, 1992;Siegert et al, 1994;Beyer et al, 1996). Of note, four patients who relapsed after HDT remain in CR at 11-55 months after either additional conventional chemotherapy/radiotherapy (two British Journal of Cancer (1998) patients) or surgical resection of residual tumour (two patients).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The most significant prognostic factor found in this study was disease status at the time of HDT; patients who had either failed to achieve an initial CR with first-line therapy or had chemotherapysensitive relapse had a significantly better outcome that those with resistant relapse. These findings concur with previous studies that have reported HDT in chemotherapy-responsive patients (Barnett et al, 1993;Margolin et al, 1996) and in patients with resistant relapse (Broun et al, 1992;Siegert et al, 1994;Beyer et al, 1996). Of note, four patients who relapsed after HDT remain in CR at 11-55 months after either additional conventional chemotherapy/radiotherapy (two British Journal of Cancer (1998) patients) or surgical resection of residual tumour (two patients).…”
Section: Discussionsupporting
confidence: 93%
“…Early mortality in previous studies of HDT has ranged from 0% to 18% (Broun et al, 1992;Rosti et al, 1992;Barnett et al, 1993;Motzer et al, 1993;Siegert et al, 1994;Margolin et al, 1996), with a finding of 8% in the largest reported group of 310 patients (Beyer et al, 1996). In this study HDT-associated death occurred in 1 of 31 patients (3%), as a result of acute renal failure, with two other patients requiring temporary haemodialysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Early experience of high-dose chemotherapy with autologous marrow or stem cell support (HDC/SCT) in multiply relapsed or refractory patients has shown that 10-15% could be saved with this approach. [4][5][6][7][8][9] We have summarized the results of our experience of high-dose chemotherapy with autologous marrow transplantation for less heavily pre-treated patients with relapsed or refractory germ cell malignancies in both men and women. This small series of patients suffering from a relatively uncommon disease illustrates that up to 52% of relapsed or refractory patients could still obtain long-term event-free survival of more than 4 years.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Initial experience with high-dose chemotherapy using carboplatin-and etoposide-containing regimens showed that 10-15% of heavily pretreated (two or more salvage chemotherapy regimens) patients could still obtain long-term remissions. [4][5][6][7][8][9] Recently, data on 283 heavCorrespondence: RA Mandanas, 920 SL Young Blvd WP2010, Oklahoma City, OK 73104, USA Received 23 June 1997; accepted 2 October 1997 ily pretreated patients with disseminated germ cell tumors from four large centers in the USA and Europe have been analyzed retrospectively for prognostic variables that predict a poor outcome with high-dose chemotherapy and hematopoietic stem cell support. 10 The resulting model categorized patients into three groups based on the number of prognostic factors present and allows the separation of poor (3-5 risk factors) risk patients from good (0 risk factors) and intermediate (1 or 2 risk factors) risk patients who might still have a beneficial outcome (27-51% 2-year failure-free survival) following high-dose chemotherapy and autologous stem cell support.…”
mentioning
confidence: 99%